The Effect of Reaction Temperature on the Structural and Magnetic Properties of Nano Cofe2o4 - Casagrande-Denardin, J (Elsevier Ltd, 2017)
Nano cobalt ferrites (CoFe2O4) were co-precipitated at various reaction temperatures (60, 70 and 80 °C) for 1 h. The reaction temperature greatly influenced the crystallite size and the magnetic behaviours of the nano CoFe2O4. The mean crystallite size ranged from 9 to 15 nm with the increase in the reaction temperature and the intensity of metal oxide vibrations at 568–550 cm−1 were also inclined. The synthesized samples were in the stoichiometric ratio of 1:2 (Co:Fe) with roughly spherical morphology. The synthesized cobalt nanoferrites exhibited ferromagnetism at room temperature and 5 K, and the saturation magnetization increased from 6.4 to 20 emu/g with the crystallite size. © 2017 Elsevier Ltd and Techna Group S.r.l.